Consensus of the Present and Prospects on Endoscopic Diagnosis and Treatment in East Asian Countries. (10th October 2012) - Kamiya, Takeshi; Joh, Takashi; Sollano, Jose D.; Zhu, Qi; Kachintorn, Udom; Aziz Rani, Abdul; Hahm, Ki-Baik; Takahashi, Shin'ichi; Kinoshita, Yoshikazu; Matsumoto, Takayuki; Naito, Yuji; Takeuchi, Koji; et al.
Abstract : Background and Aim . New diagnostic or therapeutic methods in endoscopy have been used. Current clinical application of these procedures is not well known. The aim of this study is to investigate the present situation on endoscopic diagnosis and treatment of gastrointestinal disorders in East Asian countries. Method . A representative member from the International Gastrointestinal Consensus Symposium Committee provided a questionnaire to physicians in China, Indonesia, Japan, Korea, the Philippines, and Thailand. Results . In total, 514 physicians including gastroenterologists, surgeons, and general practitioners enrolled. The most frequently occurring disorder as the origin of upper gastrointestinal bleeding is gastric ulcer. Capsule endoscopy is selected as the first choice for the diagnosis of small intestine bleeding. The second choice was double-balloon endoscopy or angiography. For patients with gastric adenoma, the number of physicians who choose endoscopic mucosal resection is larger than those selecting endoscopic submucosal dissection (ESD) in China, Indonesia, the Philippines, and Thailand. ESD is chosen first in Japan and Korea. Conclusion . New instruments or techniques on endoscopy have not come into wide use yet, and there is diversity in the situation on it in Asian countries. We should unify the endoscopic diagnostic criteria or treated strategy in patients with GI disease.